Solar/visible light photocatalytic dye degradation using BaTi1−xFexO3 ceramics. Issue 8 (3rd May 2022) - Gaur, Akshay; Sharma, Moolchand; Chauhan, Vishal Singh; Vaish, Rahul
Abstract: BaTi1− x Fe x O3 compositions (for x  = 0, 0.1, and 0.2) were prepared via a solid‐state reaction route. The presence of iron (Fe) in barium titanate (BaTiO3 ) eventually decreased the energy bandgap; thus, its utilization for water cleaning application through photocatalysis process was explored (using methylene blue [MB] dye as an indicative pollutant in water). Characterization of the synthesized powder was performed through scanning electron microscopy, X‐ray diffraction, Raman spectroscopy, and X‐ray photoelectron spectroscopy. The bandgap of the synthesized powder was calculated as 3.2, 2.12, and 1.67 eV for BaTi1− x Fe x O3 compositions (for x  = 0, 0.1, and 0.2), respectively. BaTi0.8 Fe0.2 O3 powder showed excellent results, and ∼71% of the MB dye (∼5 mg/L concentrated) was degraded using the photocatalysis process under visible light. To check the potentiality of BaTi1− x Fe x O3 compositions (for x  = 0, 0.1, and 0.2), the photocatalysis process was carried out by changing the concentration of MB dye (2.5–10 mg/L with a step of 2.5 mg/L) and the amount of BaTi0.8 Fe0.2 O3 powder (0.05–0.2 g with a step of 0.05 g) for ∼5‐mg/L concentrated MB dye. The treated water was further used as a growth parameter and phytotoxicity analysis through germination index on the wheat seeds. Lastly, the BaTi1− x Fe x O3 compositions (for x  = 0, 0.1, and 0.2) were explored for water cleaning applications under real‐time solar irradiation.